Effect of Melagatran on Prothrombin Time Assays Depends on the Sensitivity of the Thromboplastin and the Final Dilution of the Plasma Sample - Mattsson, Christer; Menschiek-Lundin, Angela; Wåhlander, Karin; Lindahl, Tomas L. (Thrombosis and Haemostasis, 2001)
Prothrombin time (PT) assays are clotting methods that measure the activity of vitamin K-dependent coagulation factors (F) II, VII, and X. There are three main types of PT assays in general usage, namely the Quick assay, Owren’s assay and PT dry chemistry test cards. PT assays were initially developed to monitor dose-adjustments of vitamin K antagonists such as warfarin. The aim of the present study was to investigate whether commercially available PT assays are suitable for evaluating the anticoagulant activity of direct thrombin inhibitors. Melagatran, a reversible direct thrombin inhibitor, was added to human plasma at concentrations ranging from 0.1 to 2.0 μmol/l. Seventeen different commercially available PT kits were used, including thirteen Quick reagents, two Owren reagents and two PT test cards. The sensitivity of the different reagents, expressed as the concentration of melagatran that doubled the prothrombin time (IC50) varied widely, with Thromboplastin S and Thromboplastin HS being the most sensitive (IC50 = 0.9 μmol/l). The reagents with apparently the lowest sensitivity were the two Owren reagents Nycotest PT and SPA 50 with an IC50 of 2.2 and 2.9 μmol/L, respectively. This is most likely due to a higher dilution of melagatran in these assays compared to the dilution in the Quick assays. The results were also dependent on the International Sensitivity Index (ISI) of each reagent. The concentration of melagatran that produced an International Normalized Ratio (INR) of 2 was calculated from dose-response curves for each assay, and these results revealed that reagents with a high ISI value gave an INR of 2 at much lower concentrations of melagatran (0.5-0.7 μmol/L) than those with an ISI-values around one (0.9-1.2 μmol/L). It was found that INR depends not only on the plasma concentration of melagatran, but also on the sensitivity of the PT reagent and on the final dilution of the plasma sample in the prothrombin time assay. Thus, since the same melagatran concentration can be associated with widely varying PT/INR results depending on the specific assay used it is concluded that PT assays and INR can not be used to monitor melagatran activity.
Keywords: Prothrombin time; melagatran; direct thrombin inhibitors; anticoagulants; thromboplastin